Anammox biofilm process using sugarcane bagasse as an organic carrier - Zulkarnaini Zulkarnaini; Puti Sri Komala; Arief Almi (Indonesian Journal of Biotechnology, 2021)
The anaerobic ammonium oxidation (anammox) biofilm process commonly uses various inorganic carriers to enhance nitrogen removal under anaerobic conditions. This study aims to analyze the performance of nitrogen removal in anammox process using sugarcane bagasse as an organic carrier. The experiment was carried out by using an up‐flow anaerobic sludge blanket (UASB) reactor for treating artificial wastewater at room temperature. The reactor was fed with ammonium and nitrite with the concentrations of 70‐150 mg–N/L and variations in the hydraulic retention time of 24 and 12 h. The granular anammox belongs to the genus Candidatus Brocadia sinica that was added as an inoculum of the reactor operation. The experimental stoichiometric of anammox for ΔNO2‐–N: ΔNH4+–N and ΔNO3‐: ΔNH4+ were 1.24 and 0.18, respectively, which is similar to anammox stoichiometry. The maximum Nitrogen Removal Rate (NRR) has achieved 0.29 kg–N/m3.d at Nitrogen Loading Rate (NLR) 0.6 kg–N/m3.d. The highest ammonium conversion efficiency (ACE) and nitrogen removal efficiency (NRE) were 88% and 85%, respectively. Based on this results, it indicated that sugarcane bagasse as organic carriers could increase the amount of total nitrogen removal by provided of denitrification process but inhibited the anammox process at a certain COD concentration.